Intra-Operative Vertebroplasty Combined with Posterior Cord Decompression: A Report of Twelve Cases. Issue 5 (September 2014) - Allegretti, Luca; Mavilio, Nicola; Fiaschi, Pietro; Bragazzi, Roberto; Pacetti, Mattia; Castelletti, Lara; Saitta, Laura; Castellan, Lucio
Percutaneous vertebroplasty (VP) is a minimally invasive technique for the treatment of vertebral pathology providing early vertebral stabilization and pain relief. In cases of vertebral pathology complicated by spinal cord compression with associated neurological deficits, VP alone cannot be performed free of risks. We describe a combined approach in which decompressive laminectomy and intra-operative vertebroplasty (IVP) are performed during a single session. Among the 252 VP performed in our centre in the past three years, 12 patients (12 vertebral levels) with different pathologies (six symptomatic haemangiomas, two metastatic fractures, four osteoporotic fractures) were treated with an open procedure combined with surgery. All cases were treated with decompressive laminectomy and IVP (mono/bipeduncular or median-posterior trans-somatic access). Five patients with symptomatic haemangiomas were treated with endovascular embolization prior to the combined approach. A visual analogue scale (VAS) was applied to assess pain intensity before and after surgery. The neurological deficits were evaluated with an ASIA impairment scale. In all cases benefit from pain and neurological deficits was observed. The mean VAS score decreased from 7.8 to 2.5 after surgery. The ASIA score improved in all cases (five cases from D to E and five cases from C to D). No clinical complications were observed. In one case a CT scan performed after the procedure showed a foraminal accumulation of PMMA, but the patient referred no symptoms. IVP can be successfully applied in different pathologies affecting the vertebrae. In our limited series this approach proved safe and efficient to provide decompression of spinal cord and dural sac and vertebral body stabilization in a single session.